First study of sperm mediated gene transfer in Egyptian river buffalo - Mohamed S. Hassanane; Aida I. El Makawy; Sahar M. Helalia; Ahmed S. Abdoon; Kamal M.A. Khalil; Tharwat A. Ghanem; Amany M. Tohamy; Xiao-Feng Sun; Wei Shen (Journal of Genetic Engineering and Biotechnology, 2017)
The present study was carried out to find the best treatments for enhancing the ration of insertion of a desired gene construct (pEGFP-N1) onto the sperm of buffalo as the first step for the production of transgenic buffalo using sperm mediated gene transfer (SMGT). The tested conditions were plasmid DNA concentration, sperm concentration, transfecting agent concentration: Dimethyle sulphoxide (DMSO) and time of transfection. The study proved that the best conditions for producing transgenic embryos were incubation sperm solution its concentration is 107/ml sperm with 3% DMSO: with 20 µg/ml from the linarized DNA, for 15 min at 4 °C are the best conditions to produce transgenic buffalo embryo using sperm mediated gene transfer.